The Konfigurasi Sistem Database Enterprise Resource Planning (ERP) Berbasis Open Source Berdasarkan Material Requirement Planning (MRP) - Regiyanda Adji Kuswara; Istantyo Yuwono (Universitas Muhammadiyah Gresik, 2021)
Cahaya Citra Alumindo is a company engaged in manufacturing. In planning raw materials, there are several problems that occur, namely production planning is still limited in its calculations because there is no structured recording available. In addition, the flow of document information in each division is still done manually, so that it can hamper the company's business processes. From the results of the study, the total net weight of car wheel products based on waste calculations was 23,150.35 kg, from the calculation of reorder points and safety stock, it was found that the raw material requirements for a 3 month period were 20,852.35kg with a lead time of 7 days, and the lowest inventory cost. low with the lot for lot method of Rp. 836,140,000. While the results of enterprise resource planning, from the validation results, the System Usability Scale (SUS) test obtained a value of 26.67 which included Acceptable, in the Grade Scale it got a value of C and Adjective. The rating gets Good, the result of the user experience of the Odoo ERP system has a User Friendly UX.